New edaphic mites of the genus Veigaia from Slovakia and Bulgaria, with a key to the European species (Acari, Mesostigmata, Veigaiidae) - Mašán, Peter; Fenďa, Peter; Mihál, Ivan (Zootaxa, 2008)
Five new European mite species (Acari: Veigaiidae) are described from the Carpathian Mountains in Slovakia and the Stara Planina Mountains in Bulgaria: Veigaia carpathica Mašán & Fenďa, sp. nov., V. incisilobata Mašán, sp. nov., V. pentachaeta Mašán, sp. nov., V. slovaca Mašán, sp. nov., and V. vermiculifera Mašán, sp. nov. Ecological information is provided for the most common and abundant species, V. carpathica and V. slovaca. A new key to the females of the European species of Veigaia is provided.